Students' Moral Intelligence in the Perspective of Peer Interaction and Self Esteem - Inggrit Puspitasari; Amanah Surbakti; Nefi Darmayanti (Psikostudia : Jurnal Psikologi, 2023)
The phenomenon in this study is the deterioration in student morale due to the influence of wrong peer interactions and low self-esteem. Thus, this study aims to reveal the influence of social interaction and self-esteem on the moral intelligence of students at SMK Negeri 13 Medan. The research method uses correlational. A random sample of 121 people. Distribution of questionnaires with Likert scale. Data analysis with multiple regression techniques. The results of data processing show that there is an influence of peer interaction on moral intelligence. So, the better the interaction with peers, the more it will increase the moral intelligence of students. There is an influence of self-esteem on moral intelligence. Increasing students' self-esteem will also increase their moral intelligence. There is an influence of peer interaction and self-esteem on moral intelligence which means together peer interaction and self-esteem affect students' moral intelligence. The influence of the two variables together raises moral intelligence by 35.6%. It is recommended that students associate with peers who can lead them to the path of goodness and have a steady self-esteem so that students have high moral intelligence for the success of their lives in the future. The implications of this research for students, carrying out peer interaction and having high self-esteem can be used in efforts to increase moral intelligence.Fenomena dalam penelitian ini adalah terjadinya kemerosotan pada moral siswa dikarenakan pengaruh interaksi teman sebaya yang salah dan harga diri yang rendah. Maka, penelitian ini bertujuan untuk mengungkapkan pengaruh interaksi sosial dan harga diri terhadap kecerdasan moral siswa di SMK Negeri 13 Medan. Metode penelitian menggunakan korelasional. Sampel secara random sebanyak 121 orang. Penyebaran angket dengan skala likert. Analisis data dengan teknik regresi ganda. Hasil olah data menunjukkan ada pengaruh interaksi teman sebaya terhadap kecerdasan moral. Sehingga, semakin baik interaksi dengan teman sebaya maka akan semakin meningkatkan kecerdasan moral siswa. Ada pengaruh harga diri terhadap kecerdasan moral. Meningkatnya harga diri siswa maka akan meningkatkan pula kecerdasan moralnya. Ada pengaruh interaksi teman sebaya dan harga diri terhadap kecerdasan moral yang mengartikan secara bersama-sama interaksi teman sebaya dan harga diri berpengaruh terhadap kecerdasan moral siswa. Pengaruh kedua variabel secara bersama-sama memunculkan kecerdasan moral sebesar 35,6%. Disarankan agar siswa bergaul dengan teman sebaya yang dapat membawa mereka ke jalan kebaikan dan mempunyai harga diri yang mantap sehingga para siswa mempunyai kecerdasan moral yang tinggi untuk keberhasilan kehidupannya ke depan kelak. Implikasi penelitian ini bagi siswa, melaksanakan interaksi teman sebaya dan mempunyai harga diri yang tinggi dapat digunakan dalam upaya peningkatan kecerdasan moral.